(untitled) (Bangladesh Journal of Nuclear Medicine, 2018)
Background: Thyroid carcinoma is rare in childhood and adolescence. The presentation is more advanced in case of children as compared to adults. However, the prognosis for survival in children is reportedly excellent. The aim of the study was to see the outcome of patients with well differentiated thyroid carcinoma during childhood and adolescence treated at a single institute. Patients and methods: A retrospective study of 61 children and adolescent patients (age ≤18years) with well differentiated thyroid carcinoma (DTC) enrolled in the National Institute of Nuclear Medicine and Allied Sciences, Dhaka during the period of January1986 up to December 2007 was carried out. To allow for a theoretical follow up of at least 5 years the last inclusion year was 2007 and follow up was carried on up to June 2013. All patients were treated by thyroidectomy followed by radioiodine ablation therapy. Whole body scans, Tg, anti Tg Ab and neck ultrasound findings were recorded six months to one year after initial therapy to classify patients into remission, persistent or recurrent disease. Status on last follow up was noted to estimate the survival rate. Results: A total of 40 patients had papillary carcinoma, 18 had follicular variant of papillary carcinoma (FVPCT) and three had follicular carcinoma. Age range at diagnosis was nine to 18 years with a mean of 15± 2 years. The number of patients ≤10 years were five and > 10 years were 56. There were 12 males and 49 females giving a M: F ratio of about 1:4. Among the 61 patients 30 patients had lymph node metastases and two had both nodal and lung metastases at initial presentation. After one year follow up from the initial radioiodine therapy, 30 patients were in remission and 31 patients had persistent disease. Eventually recurrence occurred in five patients. Three patients died during the whole observation period and all of them were cancer related giving a cancer specific mortality ratio of 0.049%, 95% CI 0 to 0.105%. Cancer specific survival by Kaplan-Meier curve was 98.2%, 98.2% and 66% at 5, 10 and 15 years respectively. Conclusion: DTC in children and adolescent has a good prognosis in the presence of neck and distant metastases. Awareness of the patient and regular follow up with life long surveillance is essential to obtain a favorable outcome. Bangladesh J. Nuclear Med. 20(2): 99-104, July 2017